Development of Cynicism in Medical Students: Exploring the Role of Signature Character Strengths and Well-Being - Kachel, Timo; Huber, Alexandra; Strecker, Cornelia; Höge, Thomas; Höfer, Stefan (Frontiers in Psychology, 2020)
Reports of medical students experiencing burnout related symptoms (e.g. cynicism) have increased in recent years. Little is known about the developmental process of this phenomenon and its relations with signature character strengths and well-being. The aim of this longitudinal analysis was to explore changes in the level of cynicism of medical students while in preclinical education. We further examined how the applicability of signature character strengths and well-being are related to this developmental process. Medical students (N = 99) participated in three online surveys over three years during medical school. Latent growth modeling, latent class growth modeling, general mixed modeling was conducted, and post-hoc mixed ANOVA, Friedman test and Welch test analyses were examined. The results showed an increase in cynicism among medical students from first to last measurement. Two groups with distinct developmental trajectory patterns of cynicism were identified. Students with high levels of cynicism (high-level group) and students with changing levels of cynicism (increasing group) perceived higher applicability of signature character strengths in private life compared to the study context. Moreover, the high-level group experienced significantly lower psychological well-being, mastery, optimism and relationship. This explorative study offers a comprehensive understanding of cynicism development in medical students during medical school and its relations to the applicability of signature character strengths and well-being. Prospective replication studies are needed to replicate the results obtained in this study.